Preaching councils and preachers among Muslims through Hisbah books - aintizar baqir muhamad husayn / aihmad hatif tahir ((Humanities, social and applied sciences) Misan Journal of Academic Studies, 2023)
The councils were and still are held in homes or official offices, in which the conferees discuss their private and public matters. These councils took upon themselves the dissemination of the sciences of scholars, poetic poems, and political and humorous news, and they were attended by various segments of society. These councils helped preserve the Arab-Islamic heritage of moral ideals and values, but because of the sectarian strife that prevailed in society in the fifth century AH, they could not change the thinking of the general public or raise their cultural level. themselves with this current.